FORM AND FUNCTION STUDY OF BARIS KEKUPU DANCE IN BANJAR LEBAH, SUMERTA KAJA VILLAGE, DENPASAR CITY - Gunarta, I Wayan Adi (Institut Seni Indonesia Denpasar, 2024)
Dance is one of the crucial aspects of the Balinese Hindu community's artistic, cultural, and socio-religious activities. Dance is referred to as the art of movement and contains aesthetic and philosophical values, which can be enjoyed by the dancers and the audience (art lovers) during the performance. In Sumerta Kaja Village, East Denpasar Subdistrict, Denpasar City, there is a Baris Dance whose shape has a speciality, namely the Kekupu Baris Dance. This article aims to describe the beauty of the form and function of Baris Kekupu Dance. The research method used is descriptive qualitative. The results showed that the Baris Kekupu Dance is a traditional Balinese dance created around 1930 by a Balinese kakebyaran artist, I Nyoman Kaler. This dance describes the movements of a group of colourful butterflies who are playing in a beautiful flower garden, happily looking for flower honey. Baris Kekupu dance was popularized by Banjar Lebah dance maestro, Ni Ketut Arini, and until now, its existence is still sustainable and has become an icon of Banjar Lebah. The uniqueness of Baris Kekupu Dance can be seen from its dance movements and costumes, which combine Legong dance movements with Baris dance movements. Furthermore, in terms of dance costumes for body decoration using awiran type costumes (Baris Dance costumes), while for headdresses using gelungan of legong dance (the type of gelungan pepudakan). Baris Kekupu Dance has two primary functions: as a ritual tool in the Dewa Yadnya (a ceremony to Gods/Goddesses) and Pitra Yadnya (ceremonial offerings to ancestors) ceremonies, and as an aesthetic presentation.